Structural, electrical and ferroelectric characteristics of Bi(Fe0.9La 0.1)O3. Issue 17 (1st December 2018) - Kumar, Nripesh; Shukla, Alok; Kumar, Nitin; Sahoo, Sushrisangita; Hajra, Sugato; Choudhary, R.N.P.
Abstract: Nowadays, much attention is paid for the development of lead-free complex or mixed metal oxides, which can be utilized for multi-functional devices. This communication provides the information on synthesis (by mixed oxide route) and physical properties (structural, electrical and ferroelectric) of the polycrystalline sample of Bi(Fe0.9 La0.1 )O3 Analysis of the phase formation and basic crystal data of the material using X-ray diffraction (XRD) technique shows an orthorhombic symmetry with well-defined cell parameters. It has been shown that a small amount (10%) of La substitution at the Fe site of BiFeO3 suppresses the impurity phase usually observed during phase formation of BiFeO3 . The average crystallite size, calculated through applying Scherrer's technique, was found to be 68 nm. For the study of surface morphology (grain size and distribution) of the compound, the scanning electron microscope (SEM) was used. The grains of different dimension were found homogeneously distributed at the entire surface of the sample. The La substitution strongly affects the capacitive (dielectric) and resistive (electrical) characteristics of bismuth ferrite in a wide range of frequency and temperature. The contributions of grains and grain boundaries in the capacitive as well as in the resistive properties of the material at different temperatures and frequencies were studied by means of the impedance spectroscopy technique. This study has provided numerous useful and interesting data which may find potential industrial applications.